Clean Water Management Assistance to Improve Clean Water Access in Pandan Lagan Village - Amanda, Julia; Musthofa, M Arif; Al Munip (Future Tecno-Science Publisher, 2025)
Access to clean water is a fundamental need, particularly in rural areas where communities still face limited infrastructure and resources. This community service program aims to enhance the capacity of local managers and villagers in managing clean water through technical and managerial mentoring. The activity was carried out in Pandan Lagan Village, Gedeg District, Mojokerto Regency, involving the village’s Water Management Group (KPA) and the surrounding community. The methods included socialization, technical training, mentoring on clean water management systems, and evaluation of behavioral and administrative changes. The results indicate an increased community awareness of water conservation, improved technical skills of water managers in maintaining pipelines and reservoirs, and the establishment of a transparent local water management structure. The program also resulted in a significant improvement in clean water access, from 64% to 91% of households receiving clean water services.